(untitled) (Third Sector Social Economic Review, 2022)
Digitalization causes changes and transformations not only in the mechanical processes of the enterprises, but also in the organizational dynamics. The digital transformation in production processes affects the working environment and includes different opportunities and risks. From this point of view, the main purpose of the study is to examine the relationship between digitalization perceptions of employees and job satisfaction, job performance and organizational commitment. A quantitative field study was conducted for the research and the necessary data were obtained through a questionnaire from the employees of the companies operating in Ankara İvedik Organized Industrial Zone. In this study, a holistic model was developed that examines the relationships between the digitalization perception and the variables of job satisfaction, job performance and organizational commitment. Structural equation modeling method was used to test the model established in the research and the hypotheses based on this model. According to the research findings, it is concluded that the perception of digitalization affects job performance and job satisfaction significantly and positively. On the other hand, according to the results of the analysis, the effect of digitalization perception on organizational commitment is positive but not statistically significant.